A CHRONOLOGICAL ANALYSIS OF INDUSTRIAL DEVELOPMENT IN UZBEKISTAN OVER THE COURSE OF 500 YEARS - Qodirov Alisherjon Akmaljon o’g’li (Ecominds Press, 2025)
The research is aimed to explore Uzbekistan’s industrial evolution - from medieval artisanal economies to contemporary reforms - examining historical limitations, post-independence transitions, and present development strategies, while projecting future growth driven by diversification, technological advancement, and deeper integration into regional and global economic systems.